Computational study of vortex shedding and its effects on asymmetrical airfoil with gurney flap - Balram Mandal; Roshani Kumari Gupta; Abhinav Adhikari; Mit Manojbhai Sheth; Rameshkumar Bhoraniya; Atal Bihari Harichandan (International Journal of Thermofluids)
The rise in airport and airline operations has increased compelling interest in aircraft noise. The aerodynamic noise initiated by the high-lifting devices is now comparable to the aircraft engine's noise. The gurney flap, a simple and easy-to-manufactured high-lifting device is suitable to study the trailing vortex shedding and its effects on generating aerodynamic noise. In the current study, the effect of adding a gurney flap on vortex shedding around the airfoil, its effect on the airfoil's aerodynamic parameters, and its effect on the generation of aerodynamic noise were observed. A numerical simulation was carried out using ANSYS Fluent for various angles of attack at Re=300 K around an Asymmetrical Airfoil, namely NACA 662–015 by varying the gurney height from 1 % to 3 % of the chord of the airfoil with 0.5 % incremen steps. For aerodynamic parameters alone 2.5% h/c gurney height was found to be the optimum gurney height when the airfoil was simulated from α=-20° to α=20° with 2° increments. For NACA 662–015, the irregular vortex pattern is perceived at a 20° angle of attack for Re=300 K. Upon simulating the airfoil for α=20° to α=28° with 2° increments, it was observed that for all the angles of attack with increasing gurney heights increases the strength of shedding, the mean values as well as amplitudes of the aerodynamic parameters. From the Strouhal number based on the Power Spectral Density amplitude of the Fast Fourier Transform (FFT) of the immediate lift coefficient, it was presented that the highest value of the Strouhal number value and Power Spectral Density amplitude was found at α=24° for all gurney heights and larger angles Strouhal number values were found to be smaller. With the help of a logarithmic scale called Sound Pressure Level (SPL), it was found that on a clean airfoil vortex, shedding emits little to no aerodynamic noise as compared to that with the gurney. While adding the gurney flap to the airfoil, the optimum gurney height, i.e., 2.5% h/c gurney height, yielded the highest (CL/CD) Max and highest aerodynamic noise. It was also found that for larger angles of attack aerodynamic noise possesses a significant far-field effect. Observing the results of the study suggests that for Micro Air Vehicles where aerodynamic noise plays a significant role smaller height of the gurney should be considered as most effective. Meanwhile, for larger Air Vehicles where aerodynamic parameters play a more important role 2.5% h/c gurney height should be considered the most effective.